Attitudes towards social oocyte freezing from a socio-cultural perspective - Schick, Maren; Sexty, Réka E.; Ditzen, Beate; Wischmann, Tewes (Geburtshilfe und Frauenheilkunde, 2017)
Introduction: The tendency to delay parenthood is increasing. It is partly driven by the availability of early reproductive technologies such as social oocyte freezing, the cryopreservation of oocytes for non-medical purposes. The goal of this study was to investigate relationships between attitudes towards social oocyte freezing and different socio-cultural backgrounds in a German sample cohort. Materials and Methods: A quantitative online questionnaire was compiled. A total of 643 participants completed the questionnaire which included items on attitudes toward social oocyte freezing, socio-demographics and items, obtained from the German DELTA Institute for Social and Ecological Research, devised to indicate specific milieus. Data were analyzed using parametric and non-parametric methods. Results: There were clear correlations between attitudes towards social oocyte freezing and socio-cultural background, gender, cohort age, fertility problems, and attitudes to fertility. Positive attitudes towards social oocyte freezing were linked to struggles with fertility, a current or general wish to have a child, and flexible, progressive and self-oriented values. Participants who preferred to become parents at a younger age tended to reject cryopreservation. Conclusions: The huge number of university graduates, persons with fertility problems, and persons from specific socio-cultural backgrounds in our sample point to distinct groups interested in reproductive technologies such as social oocyte freezing. The investigated differences as a function of socio-cultural background suggest that more research into the desire to have children in German society is needed. In conclusion, it may be necessary to develop targeted family planning interventions to prevent affected women from buying into a false sense of security, thereby risking unwanted childlessness.